2013
DOI: 10.1111/avsc.12023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant community composition and flowering phenology on honeybee foraging in Mediterranean sylvo‐pastoral systems

Abstract: Questions Which are the most effective plant communities for honeybee foraging and honey production in Mediterranean sylvo‐pastoral systems? What is the relationship between flowering phenology and pollen occurring in honey sediments? Location Mediterranean sylvo‐pastoral system in Gallura, Sardinia, Italy. Methods Phytosociological and phenological surveys were performed in a circular area of 1.5 km radius with a small apiary placed in the centre. Polleniferous and nectariferous values of plant communities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The daily changes in flower abundances were 6% in our study, and it can be very different across various biotopes or seasons. Seasonal changes in flower abundances were also found by others (Kubo et al 2008;Bagella et al 2013;Hicks et al 2016). Pollinators necessarily follow the changes in the temporal distribution of flowering phenology (Goulson 1999;Potts et al 2004;Kubo et al 2008).…”
Section: Temporal Changessupporting
confidence: 59%
See 1 more Smart Citation
“…The daily changes in flower abundances were 6% in our study, and it can be very different across various biotopes or seasons. Seasonal changes in flower abundances were also found by others (Kubo et al 2008;Bagella et al 2013;Hicks et al 2016). Pollinators necessarily follow the changes in the temporal distribution of flowering phenology (Goulson 1999;Potts et al 2004;Kubo et al 2008).…”
Section: Temporal Changessupporting
confidence: 59%
“…Pollinators consume floral nectar, pollen and oils, while sexual reproduction of plants depends on pollen transfer by pollinators (Goulson 1999;Nicolson et al 2007;Patiny 2012). In natural circumstances, plant-pollinator interactions may rapidly change at the spatio-temporal scale (Kubo et al 2008;Fründ et al 2011;Bagella et al 2013), and food resources can be highly aggregated in space or time (Elzinga et al 1998;Hatfield & Lebuhn 2007). Floral food resource quality, quantity and production rates show a huge variation with plant species, time of the day, age of flowers and competitors' consumption (Galetto & Bernardello 2004;Nicolson et al 2007;Hicks et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The climate is typically Pluviseasonal oceanic low meso-Mediterranean low subhumid (Worldwide Bioclimatic Classification System, 1996) with a mean annual rainfall of 630 mm (70% from October to March), mean annual temperature of 14.2 °C, and aridity index (rain / reference evapotranspiration on an annual basin) of 0.53. The area is representative of the climate, vegetation type, and management of some of the most common agroforestry systems in the Mediterranean basin (Bacchetta et al, 2009;Bagella et al, 2013). The potential vegetation in the sampled areas would be a Quercus suber forest (Bagella and Caria, 2011) and the dominant landscape of the area is a mosaic of vineyards for the production of Vermentino DOCG wine and wooded hay-land or pasture (dehesa-like landscape).…”
Section: Site Descriptionmentioning
confidence: 99%
“…A bias in the detection of individual specialisation in resource use may occur when individuals from a population live during different time windows within a season (also referred to as 'temporal fragmentation ' Nowicki et al 2005, Bubová et al 2016, and where resource availability to individuals in the population changes over time, as may be the case for many insect pollinators and their floral resources (Ogilvie and Forrest 2017). Temporal variation in the occurrence of individuals is likely to result in an apparent individual specialisation in resource use of insect pollinators, because floral resources change rapidly (Kubo et al 2008, Bagella et al 2013, Szigeti et al 2016, and individuals living in different stages of the flight period (Calabrese and Fagan 2004, Nowicki et al 2005, Calabrese et al 2008, Bubová et al 2016) encounter different floral compositions (Ogilvie and Forrest 2017). Although Ogilvie and Forrest (2017) suggested that this pattern occurs frequently in plant-pollinator interactions, this assumption has not been corroborated in field studies.…”
Section: Introductionmentioning
confidence: 99%